Maximising struvite recovery from real wastewater sources - Thomas, David J. L. (Cranfield University, 2007)
Formation of struvite (MgNFLjPCU.ôFfeO) in reactors is proposed to limit struvite problems in sewage treatment works (STW) and offer a method of phosphorus recovery and recycling. Four sites of interest were identified by Severn Trent Water Ltd: Derby, Wanlip, Stoke Bardolph STW and Coleshill sludge destruction plant for their potential to produce struvite. Initial tests on sludge liquors collected from the four sites showed that >80% of initial orthophosphate could be removed when the Mg:PC>4 ratios was adjusted to >2:1 for Wanlip, Stoke Bardolph STW and Coleshill at pH 9. Two reactor types, a fluidised bed reactor (FBR) and a stirred tank reactor, were trialled in Phase 1 testing with Wanlip STW liquors. The FBR was able to achieve a >90% orthophosphate removal with Mg additions of 3.5 to 5 mmol but produced a suspended solid content of -300 mg L"1. To overcome the problem of ‘fines’ a metallic mesh accumulation device was fitted to the reactor. The mesh system was able to reduce the suspended solids within the liquors <50mg L' 1 when the reaction time was increased from two to three hours. The stirred tank reactor was able to remove on average 55% of the phosphate content of the liquors with a magnesium addition of 5mmol. In Phase 2 testing both types of reactor were run side-by-side in a continuous operation. In the three experiments carried out the initial orthophosphate concentration was adjusted to 95 mg L' 1 (Immol). The stirred tank reactor was able to consistently remove -65% of the influent orthophosphate concentration in the 3 experiments at a Mg:P0 4 ratio of 3.5:1. The FBR removal steadily improved from 25% to 65% over the 3 experiments. The metallic mesh system was further trialled here and successfully captured 4.1 g of struvite. A cationic polymer, polyDADMAC, was also tested for the capture of fines with less success than in previous reports. The precipitate from each reactor was analysed with SEM-EDS and XRD. The FBR produced relatively pure struvite and stirred tank a struvite and amorphous material mixture.